Pelatihan Manajemen Usaha, Kewirausahaan Dan Inovasi Buah Salak Pada Kelompok Tani Wadio Kota Nabire - Westim Ratang; Vince Tebay (UNIVERSITAS CENDERAWASIH, 2020)
This issue arises in line with the increasingly complex and uncertainty-filled business environment in recent times and into the future. Therefore, it is necessary to pursue sustainable programs to foster business mentality and culture, product design creativity, absorption of technological advances, and managerial knowledge and skills by the demands of a changing business environment. The purpose of the research is: (1) Developing and improving business management, entrepreneurship, and innovation of salak fruit in sp 3 farmer group in Wadio village of Nabire City, (2) Improving skills in processing salak fruit into salak candied products, dried candied salak and salak chips that are ready to be sold and knowledge of management of small businesses in sp 3 farmer group in Wadio village of Nabire City. The results showed that. (1) This activity can develop and improve business management, entrepreneurship, and innovation of salak fruit in sp 3 farmer group in Wadio village, Nabire City. (2). This activity can improve the skills in processing salak fruit into candied salak products, dried sweets salak, and salak chips that are ready for sale and knowledge of management of small businesses in the SP 3 farmer group in the village of Wadio Nabire City. (3). The result of participants' response to this activity is generally agreed and strongly agree with the material provided, the benefits are felt, can foster entrepreneurial interest, willing to try to innovate, and this activity is expected to have an impact on farmers' income by trying to innovate products.